Pleural plaques and pleural changes among lung cancer patients exposed to asbestos - Aziza Ghanie Icksan; Canti Widharisastra; Anna Suraya; Martina Ferstl (Universa Medicina, 2022)
BackgroundIndonesia is one of the world's largest asbestos importing countries. While asbestos is the main contributor to work-related lung cancer, studies or reports regarding the CT findings of asbestos-related lung cancer have been limited in the country. The objective of this study was to compare CT findings of the size of the tumor and pleural and lung parenchymal changes between lung cancer patients exposed to asbestosis and those not exposed. MethodsThis cross-sectional study involved 96 lung cancer patients consisting of 48 subjects who had been exposed to asbestos and 48 who had not been exposed. They underwent thoracic CT scans at the Radiology Department of Persahabatan Hospital. Asbestos exposure was determined using interviews that followed a protocol similar to that of a previous study about asbestos-related lung cancer. Senior radiologists investigated the existence of pleural and parenchymal changes. An independent T- test and chi-square test to compare CT scan features between the two groups. ResultsThe mean age was 57.75 ± 8.56 years in the asbestos-exposed group and 58.56 ± 7.99 years in the unexposed group. The proportion of tumor sizes of more than five cm, pleural plaques, and subpleural dot-like or branching opacities were significantly higher among asbestos-exposed subjects compared to the non-exposed group (p = 0.044;p=0.37;p=0.041, respectively). ConclusionsAsbestos exposure is significantly related to the size of the tumor and the existence of pleural plaques and asbestosis. These findings may help further management of lung cancer patients and the policy of asbestos use in Indonesia.